Forest management can mitigate negative impacts of climate and land-use change on plant biodiversity: Insights from the Republic of Korea. (15th June 2021) - Choi, Yuyoung; Lim, Chul-Hee; Chung, Hye In; Kim, Yoonji; Cho, Hyo Jin; Hwang, Jinhoo; Kraxner, Florian; Biging, Gregory S.; Lee, Woo-Kyun; Chon, Jinhyung; Jeon, Seong Woo
Abstract: Over the past century, the decline in biodiversity due to climate change and habitat loss has become unprecedentedly serious. Multiple drivers, including climate change, land-use/cover change, and qualitative change in habitat need to be considered in an integrated approach, which has rarely been taken, to create an effective conservation strategy. The purpose of this study is to quantitatively evaluate and map the combined impacts of those multiple drivers on biodiversity in the Republic of Korea (ROK). To this end, biodiversity persistence (BP) was simulated by employing generalized dissimilarity modeling with estimates of habitat conditions. Habitat Condition Index was newly developed based on national survey datasets to represent the changes in habitat quality according to the land cover changes and forest management, especially after the ROK's National Reforestation Programme. The changes in habitat conditions were simulated for a period ranging from the 1960s to the 2010s; additionally, future (2050s) spatial scenarios were constructed. By focusing on the changes in forest habitat quality along with climate and land use, this study quantitatively and spatially analyzed the changes in BP over time and presented the effects of reforestation and forest management. The results revealed that continuous forest management had a positive impact on BP by offsetting the negative effects of past urbanization. Improvements in forest habitat quality also can effectively reduce the negative impacts of climate change. This quantitative analysis of successful forest restoration in Korea proved that economic development and urbanization could be in parallel with biodiversity enhancement. Nevertheless, current forest management practices were found to be insufficient in fully offsetting the decline in future BP caused by climate change. This indicates that there is a need for additional measures along with mitigation of climate change to maintain the current biodiversity level. Graphical abstract: Image 1 Highlights: Combined impacts of multiple drivers on biodiversity were quantitatively evaluated. Biodiversity persistence were analyzed and projected from the 1960s to the 2050s. Reforestation enhanced biodiversity by offsetting the negative effect of urbanization. Improvements in forest habitat quality reduces the negative impacts of climate change. However, further measures are required to maintain the current biodiversity level.